A perspectiva de Rodrigo de Castro sobre as características do sangue menstrual - Melo, António Maria Martins (2021)
The discussion on the characteristics of menstrual blood is a prominent topic in the gynaecological work by Rodrigo de Castro. In this paper, we aim to analyze the arguments set forth by the author and examine the key points of the reflection on menstruum signalling the construction of his opinion. Castro proves to be an attentive and critical reader of the tradition, summarizing the conventional views on the subject and providing a conceptual framework according to which menstrual blood is positively considered.